New progress in theory and technology of electromagnetic radiation in coal and rock - HE Xueqiu; WEI Menghan; SONG Dazhao; LI Zhenlei; QIU Liming; HE Shengquan; MAJID Khan; WANG Anhu (Meitan kexue jishu, 2023)
As an important basic energy and industrial raw material in China, the safe mining of coal is the key to ensuring the national energy security and supporting the stable development of economy and society. With the gradual depletion of shallow coal resources, deep mining has gradually become the new normal of coal resource development in China, and the risk of coal- rock dynamic disasters has risen, which seriously restricts the safety and efficiency of coal mining, and has caused adverse effects on the sustainable development of coal industry. Accurate and reliable monitoring methods are considered as the prerequisite for the prevention and control of coal-rock dynamic disasters. Geophysical methods are widely used in the early warning of coal and rock dynamic disasters by sensing the acoustic, electrical, magnetic and other physical signals released during the deformation and failure process to retrieve the damage and failure state of coal and rock mass. Among those methods, the electromagnetic radiation method is a non-invasive, non-destructive, real-time and strong precursory technique suitable for the development requirements of mine informatization and intellectualization. Therefore, the development of electromagnetic radiation monitoring technology is of great significance for the prevention and control of coal and rock dynamic disasters and can provide important technical support for the construction of intelligent mines. The research achievements of electromagnetic radiation theory and technology are summarized in three aspects: experimental phenomena, mechanism models and technical methods. The discovery process of electromagnetic radiation phenomenon is reviewed. The signal characteristics, influencing factors, electromechanical coupling effects and other electromagnetic radiation characteristics of coal-rock are analyzed. According to the correlation between typical electromagnetic radiation mechanism models, stress action and crack propagation process, a classified review is made. The existing coal and rock electromagnetic radiation monitoring and early warning equipment and technical methods are then briefly introduced. On this basis, the new progress made in recent years is described in detail, including the research on vector characteristics of electromagnetic radiation, micro-scale verification of electromagnetic radiation mechanism, and electromagnetic positioning technology of coal-rock fracture. It summarizes the two current theoretical and technical research bottlenecks that the mechanism is not fully revealed and the location of disaster-prone areas cannot be achieved. Finally, a new target for the future development of electromagnetic radiation theory and technology is proposed.